Smart logos: a user’s dashboard for the visualisation of meaningful brand experience data - Lelis, Catarina (InfoDesign, 2021)
Logos have long been transporting the brand promise, which is confirmed by the carefully defined experiences the audiences have with brands. However, the new paradigms of interaction brought by social media, machine learning and big data have been shifting the power to the audiences, who are increasingly demanding less massified content and more hyper-personalised experiences. Brands have been adapting with flexible approaches, some of them made visible through their dynamic visual identities in which the logos transmogrify in some of their components, rather than being consistently static. In this research, the possibility of dynamic logos becoming smart logos — through which the brands’ audiences/users can define their experiences by visualising personally meaningful brand-related data — is explored. Five creative workshops with users from three university campuses based in the United Kingdom were organised. The created outputs were analysed, and they evidence what is both considered meaningful content and the most natural logo variation mechanisms for data to be displayed and consumed. Finally, a heuristic to support the design of smart logos is proposed and the conceptual model that underpins it and that allows answering the research question is presented.